Anodic Performance of BaO-Added Ni/SDC for Solid Oxide Fuel Cell Fed With Dry CH4 - Itagaki, Yoshiteru; Yamaguchi, Syuhei; Yahiro, Hidenori (Frontiers in Energy Research, 2021)
SOFCs fed with dry H2 and CH4 fuels were examined using 20 wt% Ni/SDC and 0.2 wt% BaO-added 20 wt% Ni/SDC [Ni(BaO)/SDC] anodes. The i–v characteristics of the cells in H2 and CH4 resulted in a higher output produced by CH4 fuel compared to that produced by H2 fuel in both anodes. In both fuels, better anode characteristics were obtained for Ni(BaO)/SDC. Consequently, the anodic performance was in the order of Ni(BaO)/SDC in CH4 > Ni/SDC in CH4 > Ni(BaO)/SDC in H2 > Ni/SDC in H2. A significant carbon deposition was observed in the Ni/SDC anode in CH4, but the carbon deposition observed in Ni(BaO)/SDC was less. From the DC electrical resistance measurement of the anode films, a remarkable decrease in resistance was observed in Ni/SDC due to the carbon deposition after CH4 exposure. The resistance of Ni(BaO)/SDC was higher than that of Ni/SDC and did not change even after CH4 exposure because of the less carbon deposit. The high dispersibility of Ni particles was confirmed in both anodes and was particularly remarkable in Ni(BaO)/SDC. The highest anodic performance in Ni(BaO)/SDC was attributed to the high Ni dispersibility which might promote CH4 decomposition by producing less carbon deposit. It was speculated that the higher cell output in CH4 than that in H2 is due to the locally high concentration of H2 and/or CO gas on the anode surface by the promotion of CH4 decomposition.